'The Most Beautiful Blue': Painting, Science, and the Perception of Coloured Shadows. (24th October 2018) - Smith, Paul
Abstract: This article examines first of all how painters' ability to perceive transient coloured shadows was both facilitated, and impoverished, by scientific theories of their causes. It then investigates how developing techniques of viewing the scene through a frame or half-closed eyes allowed artists to apprehend these elusive phenomena in something approaching their full richness.